On the stress investigation at the edges of the fixed elastic semi-strip - N. Vaysfeld; O. Kryvyi; Z. Zhuravlova (Fracture and Structural Integrity)
The stress state of the elastic fixed semi-strip with the regarding of the singularities at its edge is investigated in the article. The initial boundary problem is reduced to a vector boundary problem in the transformation’s domain by the use of integral Fourier transformation. The one-dimensional vector boundary problem is solved exactly with the help of matrix differential calculations and Green’s matrix apparatus. The problem’s solving was focused at the solving of the singular integral equation (SIE) with the two fixed singularities at the ends of the integration’s interval. The symbol of SIE was constructed and the generalized method of the SIE solving was applied. The stress’ distributions of the semi-strip are investigated.